Co : CdS diluted magnetic semiconductor nanoparticles: radiation synthesis, dopant-defect complex formation, and unexpected magnetism - Bogle, Kashinath A.; Ghosh, Saurabh; Dhole, Sanjay D.; Bhoraskar, Vasant N.; Fu, Lian-feng; Chi, Miao-Fang; Browning, Nigel D.; Kundaliya, Darshan; Das, Gour P.; Ogale, Satishchandra B. (Chemistry of Materials, 2008)
Incorporating a dopant into a nanoparticle is a nontrivial proposition in view of the size dependent surface versus bulk energy considerations and the intrinsic proximity of the surface to the interior, which facilitates migration to the surface. If realized and controlled, however, it can open up new avenues to novel nanomaterials. Some previous studies have shown the dopability of nanosystems but only with specific surface functionalization. Here, we demonstrate the successful dopant incorporation via a new route of pulsed high energy electron induced synthesis. We choose a system Co:CdS (dilutely cobalt doped cadmium sulfide) in view of the well-known application-worthy properties of CdS and the potential possibility of its conversion to a diluted magnetic semiconductor of interest to spintronics. By using various techniques, we show that matrix incorporation and uniform distribution of cobalt are realized in US nanocrystals without the need for additional chemical or physical manipulation. Optical and photoluminescence properties also support dopant incorporation. Interestingly, although magnetism is realized, it is weak, and it decreases at higher cobalt concentration. First principle density functional calculations are performed to understand this counterintuitive behavior. These calculations suggest that the introduction of parent cation or anion vacancies lead to magnetic moment reduction, albeit marginally. However, with some Co impurity fraction in the octahedral interstitial site inside the wurtzite cage, the magnetic moment drops down drastically. This study reveals that defect states may have an interesting role in dopant stabilization in nanosystems, with interesting system dependent consequences for the properties.